RELATIONSHIP BETWEEN AGE AND HISTOPATHOLOGICAL TYPE OF MENINGIOMA ACCORDING TO THE WORLD HEALTH ORGANIZATION (WHO) - Meta Zulyati Oktora; Ruhsyahadati; Debie Anggraini; Alzeri Fajar Sirfa (Yayasan Nusantara Hasana Berdikari, 2024)
Background: Meningiomas are the second most common intracranial tumors. The 2016 WHO classification divides the histopathological types of meningiomas into benign (WHO grade I) and malignant (WHO grade II or III). Benign meningiomas are characterized by a well-defined mass adhering to the dura mater and compressing the brain, whereas malignant meningiomas, though rare, are aggressive. Age is a factor that could influence the histopathological type of meningiomas, with incidence increasing with age. Meningiomas commonly occur in middle and old age, peaking in the sixth decade. Age is also a prognostic factor in meningioma occurrences. Method: This was an observational analytic study with a retrospective cross-sectional design on the medical records of meningioma patients at the Anatomical Pathology Laboratory of Dr. M. Djamil Padang Hospital from May 2023 to January 2024. The study included a total of 72 patients. Results: The Chi-Square test showed a p value of 0.330 (p>0.05), indicating no significant relationship between age and the histopathological type of meningiomas. Most meningioma patients were ≥40 years old (76.4%) and female (87.5%). The predominant histopathological type was WHO grade I (88.9%), with tumors ≤5 cm in size (65.3%). Conclusions: There is no significant relationship between age and the histopathological type of meningiomas according to WHO criteria.